2004
DOI: 10.1144/gsl.sp.2004.224.01.02
|View full text |Cite
|
Sign up to set email alerts
|

Shear zones in the upper mantle: evidence from alpine- and ophiolite-type peridotite massifs

Abstract: There is abundant field and microstructural evidence for localization of deformation in alpine-and ophiolite-type mantle massifs. On the basis of field relationships and microstructures we recognize two types of tectonite shear zones (medium-to coarse-and fine-grained), as well as two types of mylonitic shear zones (anhydrous and hydrous peridotite mylonites). In tectonite shear zones, softening processes responsible for localization are probably melt-related weakening in the medium to coarse tectonites and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 61 publications
2
14
0
Order By: Relevance
“…[]; Lanzo: Kaczmarek and Müntener [, ] and Kaczmarek and Tommasi []; Othris: Dijkstra et al . []; Lizard ophiolite; Allerton and Macleod []; and Josephine: Kelemen and Dick []), suggesting deformation in the vicinity of a thermal anomaly [ Vauchez et al ., ], a hypothesis which has recently been supported by geophysical surveys using SKS‐wave splitting in the active rift setting of the Afar (Ethiopia) region [ Hammond et al ., ]. As shown by experimental investigations, the presence of melt reduces the harzburgite's flow strength [ Hirth and Kohlstedt , ; Zimmerman and Kohlstedt , ] forcing deformation to localize.…”
Section: Discussionmentioning
confidence: 99%
“…[]; Lanzo: Kaczmarek and Müntener [, ] and Kaczmarek and Tommasi []; Othris: Dijkstra et al . []; Lizard ophiolite; Allerton and Macleod []; and Josephine: Kelemen and Dick []), suggesting deformation in the vicinity of a thermal anomaly [ Vauchez et al ., ], a hypothesis which has recently been supported by geophysical surveys using SKS‐wave splitting in the active rift setting of the Afar (Ethiopia) region [ Hammond et al ., ]. As shown by experimental investigations, the presence of melt reduces the harzburgite's flow strength [ Hirth and Kohlstedt , ; Zimmerman and Kohlstedt , ] forcing deformation to localize.…”
Section: Discussionmentioning
confidence: 99%
“…Relatively to mantle shear zones mapped in other peridotite massifs (cf. review by Dijkstra et al [2004]), the northern Lanzo shear zone has two advantages: (1) it records the evolution of deformation under a large range of continuously varying temperature conditions, from near‐solidus conditions representative of the lithosphere‐asthenosphere boundary to fully lithospheric temperatures (800–900°) and (2) the massif is large enough allowing the exposure of the entire shear zone and of the protoliths on both sides of it.…”
Section: Discussionmentioning
confidence: 99%
“…Large‐scale mylonitic shear zones were nevertheless mapped in some orogenic massifs, like Ronda and Beni Bousera in the Betic‐Rifean belt (S Spain–N Morocco), Erro‐Tobio in the Alps, and Turon de Tecouere in the Pyrenees, and in the Othris, Voltri, and Oman ophiolites (cf. review by Dijkstra et al [2004]). A common characteristic of these mylonitic zones, shared by the northern Lanzo shear zone, is that they record an evolution under variable pressure and temperature conditions, associated to mantle exhumation in response to lithospheric thinning in extensional settings (orogenic massifs) or obduction (ophiolites).…”
Section: Discussionmentioning
confidence: 99%
“…Variations over more than one order of magnitude, from 0.01 cm to several cm, characterize mantle samples (Boyd & Meyer 1979). At a larger scale, it is generally found that areas that were subjected to major strains, such as collisional areas in the shallow lithospheric mantle, show, on average, smaller grain sizes (Dijkstra et al 2004). Overall, an average diameter of the rock matrix from available upper-mantle samples can be estimated at around 0.1 cm (Boyd & Meyer 1979), though larger diameters, for example, ∼1 cm and more, are not inconsistent with rheology.…”
Section: Grain Sizementioning
confidence: 99%